Effect of lentil bean in production of lentil biscuit / Siti Nur Amirah Azuddin - Azuddin, Siti Nur Amirah (2008)
According to popularity and high demand to the biscuit, this project was carried out in order to find the most acceptable proportion of lentil bean in biscuit that fulfill consumer acceptance. Basic formulation of biscuit was developed by addition of lentil bean. A biscuit with proportion of 20% lentil bean was found to be the most acceptable through sensory evaluation by panelist. Evaluation of mechanical properties of biscuit showed that hardness of biscuit decreased with increased proportion of lentil bean in biscuit formulation. Determination of fracturability by using texture analyzer TAXT2 indicated that there were textural changes in baked biscuit with addition of lentil bean in biscuit formulation. The results showed that the hardness, fracturability and breaking point of baked biscuit decreased as the proportion of lentil bean increased in biscuit formulation. Determination of color by Minolta Calorimeter CR-300 showed that lentil bean did not affect the biscuit colour even with high proportion of lentil bean added to the biscuit formulation. Evaluation of correlation between sensory evaluation of texture parameter and texture analysis with different proportion of lentil bean showed hardness of biscuit positively correlated with hardness, breaking point and fracturability of final baked biscuit. Evaluation of correlation between sensory evaluations of color parameter with color measurement by calorimeter showed that there were positively correlation between color of sensory evaluation and instrumental analysis. This study revealed that, biscuit with addition of lentil bean was acceptable. Biscuits with addition of lentil bean could be used to produce high protein biscuit.